Youth and Community Engagement in the Organized Health and Physical Activities in Lake Sebu, South Cotabato - Christine Joy E. Ngag; Ian Dave P. Aquino; Krystel Mae C. Satur; Emy A. Morbo; Vivencio L Calixtro Jr (Universitas Pendidikan Indonesia (UPI), 2022)
This study aimed to examine the role of the community in the development of the youth, as well as the participation of the community to address the needs of the youth pertaining to health-related and physical activities both in and out of school. This study was driven: (1) examine the role of the community to the physical and health-related activities of the youth, (2) determine the level of the engagement of the youth and the community pertaining to health-related and physical activities, and (3) introduce a new framework to strengthen the programs proposed to widen the scope of awareness of physical and health-related activities. This study used a descriptive research design with a survey questionnaire in collecting data from thirty youth ages 12-24 years. Findings show that the level of physical activities of the youth is high. They engaged in an average level considering their health-related practices. There is a high engagement of the community to the youth’s physical activities in terms of their motivation, participation, and attitude. We concluded that the youth is actively engaging in any physical activities because of the support of their community in terms of their motivation, participation, and to their attitude. However, the youth are uncertain in terms of their health-related activities, ensuring they do not have a hereditary disease, got confined to a hospital, and even use illegal drugs.